Lung inhomogeneities, inflation and [18F]2-fluoro-2-deoxy-D-glucose uptake rate in acute respiratory distress syndrome. Issue 1 (22nd October 2015) - Cressoni, Massimo; Chiumello, Davide; Chiurazzi, Chiara; Brioni, Matteo; Algieri, Ilaria; Gotti, Miriam; Nikolla, Klodiana; Massari, Dario; Cammaroto, Antonio; Colombo, Andrea; Cadringher, Paolo; Carlesso, Eleonora; et al.
The aim of the study was to determine the size and location of homogeneous inflamed/noninflamed and inhomogeneous inflamed/noninflamed lung compartments and their association with acute respiratory distress syndrome (ARDS) severity. In total, 20 ARDS patients underwent 5 and 45 cmH2 O computed tomography (CT) scans to measure lung recruitability. [ 18 F]2-fluoro-2-deoxy-d -glucose ([ 18 F]FDG) uptake and lung inhomogeneities were quantified with a positron emission tomography-CT scan at 10 cmH2 O. We defined four compartments with normal/abnormal [ 18 F]FDG uptake and lung homogeneity. The homogeneous compartment with normal [ 18 F]FDG uptake was primarily composed of well-inflated tissue (80±16%), double-sized in nondependent lung (32±27% versus 16±17%, p<0.0001) and decreased in size from mild, moderate to severe ARDS (33±14%, 26±20% and 5±9% of the total lung volume, respectively, p=0.05). The homogeneous compartment with high [ 18 F]FDG uptake was similarly distributed between the dependent and nondependent lung. The inhomogeneous compartment with normal [ 18 F]FDG uptake represented 4% of the lung volume. The inhomogeneous compartment with high [ 18 F]FDG uptake was preferentially located in the dependent lung (21±10% versus 12±10%, p<0.0001), mostly at the open/closed interfaces and related to recruitability (r 2 =0.53, p<0.001). The homogeneous lung compartment with normal inflation and [ 18 F]FDG uptake decreases with ARDS severity, while the inhomogeneous poorly/not inflated compartment increases. Most of the lung inhomogeneities are inflamed. A minor fraction of healthy tissue remains in severe ARDS. In ARDS the healthy lung regions decrease with severity. The nonhomogeneous lung regions are always inflamed. http://ow.ly/S5SOL